Resource recovery from wastes : towards a circular economy - Macaskie, Lynne E.; Sapsford, Devin J.; Mayes, Will M. (RSC green chemistry series ;, 2020)
Bringing together a broad range of topics on resource recovery this book provides a valuable resource for those working in green chemistry and waste management.